2019
DOI: 10.1080/15538362.2019.1653810
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Modeling and Predicting Quality Parameters of Fruits and Vegetables during Postharvest Storage: A Review

Abstract: Artificial neural network (ANN), genetic algorithm (GA), fuzzy logic (FL), and adaptive neurofuzzy inference system (ANFIS) have been applied in every aspect of food science in the recent years. These models are useful tools for fruit and vegetable monitoring; grading and classification; modeling the respiration rate; predicting and modeling quality properties; modeling of microbial growth; and forecasting chemical, physical, and sensorial characteristics during processing and postharvest storage. These models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Fortunately, there are novel methods that can help to understand the functioning of nanoparticles in crops and their impacts in the medium and long term. These include the application of artificial intelligence, optimization algorithms, and artificial neural network models [ 58 , 59 , 60 , 61 , 62 ] that can be excellent tools for the study of nanotechnology in agriculture and in fruit quality.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there are novel methods that can help to understand the functioning of nanoparticles in crops and their impacts in the medium and long term. These include the application of artificial intelligence, optimization algorithms, and artificial neural network models [ 58 , 59 , 60 , 61 , 62 ] that can be excellent tools for the study of nanotechnology in agriculture and in fruit quality.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that these approaches are able to estimate the drying kinetics of various fruits and vegetables with high precision. It has been shown that nonlinear approaches based on ANN are far better in generalization and estimation in comparison to empirical models (Bahramparvar et al, 2014;Salehi, 2020b;Zhang et al, 2014). Determination of the best number of neurons in hidden layers of ANN models is generally carry out by trial and error.…”
mentioning
confidence: 99%
“…Genetic algorithm is the search technique for optimal value, mimicking the mechanism of biological evolution. It has a high capability to find the optimum value of a complex objective function, without falling into local optima (Ramzi et al, 2015;Salehi, 2020b).…”
mentioning
confidence: 99%
See 2 more Smart Citations